Acoustics and the performance of music : manual for acousticians, audio engineers, musicians, architects and musical instruments makers - Meyer, Jürgen 1933- (Modern acoustics and signal processing / editor-in-chief William M. Hartmann, 2009)
This classic reference on musical acoustics and performance practice begins with a brief introduction to the fundamentals of acoustics and the generation of musical sounds. It then discusses the particulars of the sounds made by all the standard instruments in a modern orchestra as well as the human voice, the way in which the sounds made by these instruments are dispersed and how the room into which they are projected affects the sounds.